Attitudes of Older Adults Towards a Blended Exercise Program - Sumit Mehra; Sumit Mehra; Bart Visser; Raoul H.H. Engelbert; Raoul H.H. Engelbert; Jantine van den Helder; Peter J.M. Weijs (Frontiers Media S.A., 2015)
Background: Meer Bewegen voor Ouderen is a Dutch umbrella organization that aims to improve the physical, social and psychological wellbeing of senior citizens. Weekly 300,000 older adults participate nationwide in community based 'gym classes'. In order to achieve the recommended amount of physical activity, the participants are stimulated to repeat the exercises outside the classroom. Aims: As part of the VITAMINE project a qualitative study was conducted in order to determine a) the motivation of the participants to join the weekly classes b) the current level of physical activity outside the classes c) the susceptibility to an additional exercise program for the home environment and d) attitudes towards technology to support such an exercise program. Method: Seven focusgroups were conducted with an average of 6 participants. During the focusgroups a semi-structured interview and brainstorming session was held. The focusgroups lasted approximately 1.5 hours. In total 41 older adults participated in the study. The results were recorded with video and afterwards transcribed and coded with software for qualitative data analysis (MAXQDA). Results: Due to technical difficulties the responses of two focusgroups were not included in the analysis. The average age of the remaining 31 participants was 74 years (SD=9). All participants were female and in general had a low education. Their motivation to participate in the weekly gym classes was to stay fit. Most participants believed this would contribute to their ability to live longer independently. However, all the participants indicated that the social aspect of the weekly classes was also a major reason for them to join. Furthermore, they indicated they had a moderate to active life style. The need to do exercises at home was acknowledged in part. Participants indicated they were willing to spend daily 15 minutes for a home-based exercise program. Some emphasized the program should be varied, whilst others preferred a fixed routine in the exercises. However, all participants expressed the need to be able to adjust the exercise program to their own need. Also, they foresaw motivation to adhere to the home-based exercise program would be an issue. Concerning technology, a minority of the subjects were skeptical and did not welcome a home-based exercise program that was supported by technology in any form. They feared it would be too complex and they would not be able to learn the necessary skills. The majority of the participants, however, were either open to the possibility or enthusiastic about the use of technology in a home-based exercise program. A tablet seemed to be a viable option. They felt it could help them with instructions (demonstration videos) and planning. The use of reminders and social interaction with peers was received with more mixed feelings. Furthermore, most of the participants objected to the possible use of fitness trackers due to privacy concern. Several participants indicated the tablet should also be able to play music during their exercises, similar to the community based exercise program. Conclusions: An additional home-based exercise program should be consistent with the motivation of the older adults to join the weekly classes; it should make clear how it can contribute to live independently for longer. Personalizing the exercise program to the preferences of the individual is key. A training to operate a device like a tablet seems crucial to overcome the anxiety some older adults have for technology. If, and how, a technology supported home-based exercise program should make use of social elements should be explored further. The results of the described focus groups, however, should be interpreted carefully. Most of the participants were not familiar with technology as tablets. For this reason it was difficult for them to identify opportunities or threats of a home-based exercise program supported by technology. In a follow-up study the researchers will present participants a prototype tablet, in part based on the outcome of the reported focusgroups, with which the older adults can interact. This will validate and extend the findings of the present study.